Molecular and cytotoxicity investigations of Phytolacca americana (l.) root, leaf, and berry extracts - Hamissou, Mijitaba; Kurdmongkoltham, Ploy (International Journal of Pharmacology and Toxicology, 2015)
Background: Pokeweed anti-viral protein (PAP) and lectin are two of the toxic components of pokeweed, Phytolacca americana, suspected of affecting free grazing livestock and small herbivorous animals.Objectives: This research aimed to investigate the antimicrobial activity of the pokeweed extracts against two bacterial strains, the gram negative Escherichia coli and the gram positive Staphylococcus aureus, to investigate the toxicity of the extracts to cells of tobacco, Nicotiana tabacum, callus, and to investigate the presence of selected toxic constituents present in pokeweed.Methodology: Pokeweed plants were identified and brought to the laboratory and separated into roots and leaves. The berries were collected later in the growing season. Aqueous extracts were obtained by homogenizing the plant parts separately in sterile water followed by centrifugation. The supernatants were filter-sterilized and used for bacterial and tobacco callus growth inhibition assays. Total cytoplasmic proteins were also obtained by homogenizing the plant parts separately in protein extraction buffer and centrifuging. The supernatants were investigated for the presence of various toxins suspected of being present in pokeweed, using western blot analyses.Results and Conclusions: Pokeweed constituents possess growth inhibitory effects to gram negative E. coli and to N. tabacum callus but not of the gram positive S. aureus, and that all three plant parts studied were rich in lectin and lectin-like constituents such as PL-A, PL-C, and PL-G. No PL-B was detected in any of the plant extracts.